Práticas de territorialização no cuidado à pessoa com sobrepeso ou obesidade na atenção primária à saúde: Uma análise do estado da Paraíba - Brandão, Joycyelly Gomes Abdala (2023)
Introduction: Obesity is classified as a chronic non-communicable and multifactorial disease in addition to being a predisposition risk factor for other diseases. Due to its exacerbated growth, comprehensive care for the health of the population is necessary. In this context, primary health care should promote initiatives related to care actions, health promotion and obesity prevention, using territorialization practices to assist on population knowledge, acting in the promotion and execution of direct actions to this group. Objective: To characterize the process of territorialization in the care of overweight or obese people in Primary Health Care (PHC/APS in Portuguese) in the state of Paraíba. Methods: cross-sectional study, connected to a population-based study, carried out with 487 professionals working in primary health care units in the state of Paraíba. Data collection happened through the application of a semi-structured online questionnaire, prepared by the Ministry of Health in partnership with project national coordinators. The data were analyzed using descriptive statistics, in which the absolute and relative frequency of the indicators were evaluated, using the SPSS software (Statistical Package for the Social Sciences), version 22.0. In this point were analyzed variables related to respondents (demographic and professional), related to basic health units and analysis of the territory. Results: The respondents, in their marjority, were women (90,6%), nurses (65,5%), working in the Family Health Units for less than 10 years (57.8%). Only a few of them claimed to evaluate the data from the Food and Nutrition Surveillance with the team (32.0%), while the majority claimed to carry out diagnostic analyzes of the territory, obtaining data through home visits (59.2%). The construction of territorial maps took place primarily through the existence of social protection programs (88.5%) and the priorities found in the maps were families with chronic non-communicable diseases (56.1%). Most of the interviewees stated selecting and prioritizing nutritional problems (70%), with discussions with the UBS internal team being the most adopted measure for this selection (69.2%); and through follow-up of the population, other demands for nutritional care were identified (32.2%). Conclusion: although there is use of territory maps, even if in a limited way, overweight or obese people are still not satisfactorily included in territorialization practices. Analyzes of food and nutrition surveillance data are still precarious, thus creating obstacles to offering comprehensive care to this population. Greater interaction is needed between the various points of primary health care, in regard to food and nutritional surveillance actions in the territory. New studies which connect the theme of territorialization and obesity are needed, in order to support the comprehensiveness of care for this population, as well as a new look at this theme outside the context of the COVID-19 pandemic, when the referred data were obtained.